Need Analysis for Problem Based Learning E-Module on The Digestive System to Improve Student’s Problem Solving and Critical Thinking Skills - Lestari, Suwarti; Harlita, Harlita; Prayitno, Baskoro Adi (Journal of Educational Sciences, 2025)
Digital transformation in the education sector has increased the demand for adaptive and technology-based teaching materials, one of which is the development of interactive e-modules. This study aims to analyze the needs of students and teachers regarding the development of a Problem-Based Learning (PBL) e-module on the digestive system material to improve students’ critical thinking and problem-solving skills. The research employed a descriptive quantitative method using a survey distributed to 72 eleventh-grade science students and 13 biology teachers in Sukoharjo Regency. The questionnaire covered aspects of technology usage, material comprehension, preferences for e-module features, and experiences with the PBL model. Results show that 56.9% of students reported learning difficulties, and only 41.67% achieved the minimum passing grade for the digestive system topic. Both students and teachers indicated high readiness and strong interest in using PBL-based e-modules. Teachers emphasized the importance of including features such as case studies, interactive videos, structured learning content, and problem-solving exercises. Therefore, the development of a PBL-based e-module is highly relevant to support a more interactive and effective biology learning experience and to foster 21st-century skills among students.